Numerical calculations of Hölder exponents for the Weierstrass functions with (min,+)-wavelets - KENOUFI, Abdelouahab; GONDRAN, Michel (Trends in Computational and Applied Mathematics, 2014)
For all function f : Rn to R one introduces (min; +)-wavelets which are lower and upper hulls build from (min; +) analysis. One shows at theoretical level and on numerical applications for the Weierstrass functions, that (min, +)-wavelets decomposition opens a non-linear branch to the multi-resolution analysis of a signal, in particular for the Hölder exponents calculation and Empirical Mode Decomposition (EMD).